Initial Open Trial of a Computerized Behavioral Activation Treatment for Depression. (May 2013) - Spates, C. Richard; Kalata, Alyssa H.; Ozeki, Satoshi; Stanton, Cory E.; Peters, Sofia
This article presents preliminary findings from use of a novel computer program that implements an evidence-based psychological intervention to treat depression based on behavioral activation (BA) therapy. The program is titled "Building a Meaningful Life Through Behavioral Activation". The findings derive from an open trial with moderate to severely depressed individuals ( N = 15) in an Intention to Treat sample. Hierarchical linear modeling (HLM) analyses revealed significant change over time on Beck Depression Inventory–Second Edition (BDI-II) scores, Revised Hamilton Depression Rating Scale scores, and significant contribution to BDI-II score variance by participant age over time, change over time in negative automatic thoughts, and change over time in BA scores. Piecewise HLM analyses revealed that significant change over time was associated uniquely with active treatment and not during 3 weeks of baseline measurement. In addition to treatment-associated significant change on all dependent measures over time, effect sizes were in the moderate to large range. Limitations are small sample size, nonrandomized control, research-recruited patients instead of purely treatment-seeking patients, possible rating bias by independent assessors who had knowledge that participants had received active treatment in this open trial, and the influence of additional services received in the post acute-treatment phase by some participants could have contributed to maintenance of gains reported for that period.